2016
DOI: 10.1021/acsami.6b10392
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Helical Nanoribbon Polydiacetylene via Supramolecular Gelation: Circularly Polarized Luminescence and Novel Diagnostic Chiroptical Signals for Sensing

Abstract: Four kinds of commercially available diacetylene (DA) monomers with different chain length, diacetylene positions were fabricated into the organogels via mixing with a chaperone gelator, an amphiphilic l-histidine ester derivative LHC18 that can help the nongelator to form gels. Upon photo irradiation with a 254 nm UV light, the white gels underwent topochemical reaction and turned into red or blue gels, depending on the DA monomer structures. Through the gel formation, the molecular chirality of LHC18 can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 58 publications
(69 reference statements)
0
58
0
Order By: Relevance
“…For example, Zhong et al prepared chiral PDA Langmuir-Blodgett films with gemini type amphiphilic diacetylene derivatives (Zhong et al, 2010). In 2016, Chen et al found that chiral L-histidine ester derivative LHC18 amphiphiles could not only help the formation of diacetylene amphiphiles gels, but also endow PDA polymers with chiral properties (Chen et al, 2016).…”
Section: Chiral Pdamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhong et al prepared chiral PDA Langmuir-Blodgett films with gemini type amphiphilic diacetylene derivatives (Zhong et al, 2010). In 2016, Chen et al found that chiral L-histidine ester derivative LHC18 amphiphiles could not only help the formation of diacetylene amphiphiles gels, but also endow PDA polymers with chiral properties (Chen et al, 2016).…”
Section: Chiral Pdamentioning
confidence: 99%
“…PDA structures have been enriched from traditional films, micelles and vesicles to 3D-PDA structures, porous structures, hydrogels, macrocyclic structures, and single-layer nanosheets (Bang et al, 2016;Chae et al, 2016;Krishnan et al, 2016;Okaniwa et al, 2016;Jordan et al, 2017;Li et al, 2017a;Romera et al, 2017;Jeong et al, 2018;Takeuchi et al, 2018;Terada et al, 2018;Heo et al, 2019;Hu et al, 2019;Seo et al, 2019;Shin et al, 2020). Great progresses have also been made in the preparation of reversible and chiral PDA (Chen et al, 2016;He et al, 2020). PDA bioprobes based on these novel structures can further increase the sensitivity and reproducibility of detection, and their detection applications have thus been expanded to a wide range of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymer-based sensors are sensitive to very minor perturbations due to amplification by a collective system response and therefore offer a remarkable advantage over small molecule-based sensors. [1][2][3][4][5][6] Polydiacetylenes (PDAs) are wellknown conjugated polymers. PDAs show stimuli-responsive blue-to-red color changes because the conformation of the conjugated backbone changes, which results in a change of the efficient conjugated length of the polymer chain.…”
Section: Introductionmentioning
confidence: 99%
“…One meritorious feature of PDA is that it displays a brilliant color change (typically blue to red) in response to physical and chemical/biochemical stimuli 2–13 . Accordingly, this stimulus‐responsive property of PDA has been extensively used for the development of colorimetric sensors 2–30 …”
Section: Figurementioning
confidence: 99%